UNSUR INTRINSIK DAN EKSTRINSIK DALAM FILM “JOKOWI” - muhamad ramdan (IKIP Siliwangi, 2020)
Film is a literary work that is audiovisual, can bring up a picture, image of motion along with sound recorded through the media, so that it has a narrative meaning that is understood by the audience. Film is considered as a very effective learning communication medium for all ages, both for the community and students. This research is based because many films are not suitable to be watched, especially for students, so that research is needed as a measure of eligibility for a film. One of the interesting films to study is the film